ANALISIS PENALARAN SOAL GEOMETRI BIDANG DATAR PADA BUKU AJAR MATEMATIKA SD - Nadya Meila Nasution; Sukmawarti Sukmawarti (Jurnal Inovasi Penelitian, 2023)
Textbooks are one of the learning resources that must be owned by an educator as a guidebook and students as a source for learning. Reasoning-based teaching materials are one way out as a solution to the problems that have been found so far. By analyzing this reasoning-based teaching material, it is expected to be able to improve students' mathematical reasoning abilities. The main purpose of this study is to analyze the type of reasoning about flat-plane geometry in elementary mathematics textbooks. This research is a descriptive research. The method in this study uses the Lithner framework. This research was conducted by grouping the questions in the book which are included in the type of flat-plane geometry questions, analyzing the questions based on the type of reasoning, describing the types of reasoning in mathematics textbooks and providing arguments and conclusions. The results of this study in the first book of Mathematics for SD/MI class IV Mediatama Publisher, some of the questions use the Imitative Reasoning type of reasoning where there are 53.33% of the questions are Imitative Reasoning type of reasoning and 46.66% of the questions are Creative Reasoning type of reasoning. The questions contained in the book are in accordance with the content standards and have been studied by students in previous lessons. Thus, the teacher must also often give questions with the type of Creative Reasoning reasoning so that students are accustomed to being faced with difficult questions when facing exams